Establishing embodied carbon coefficients an application to housing design in Mindanao - Dojo, Darold B. (2019)
The aim of this study is to establish the embodied carbon coefficients (ECc) of construction materials used on low-cost housing units. With the established coefficients, existing housing units in Davao Region were assessed based on their EC content. The researcher then developed low-cost housing units by minimizing the embodied carbon impact of construction materials used. The identification of the materials were based on a census conducted by the National Statistics Office (NSO) last 2010. The processes of production of these materials were acquired from large companies within Davao Region. This study showed that the construction materials with numerous steps in production had the highest ECc. Among these includes: steel in general, glass, ceramics tiles, and cement. Meanwhile, low ECc materials are those that are readily available and/or involve minimal processes in production. These include wood in general, nipa, bamboo, amakan and coco lumber. The research also identified that most low-cost housing in Mindanao has an EC content that ranges from 30,000 - 40,000 Kg of carbon dioxide per 36.68 sq.m. average floor area. This is due to the fact that high ECc materials were used in high volume as compared to the low ECc ones. This study proposed modifications on the said houses which reduces the EC content of a unit upto 1/3 of the actual. Lastly, by integrating all the analyzed data, the researcher developed a low embodied carbon low-cost subdivision to be located on Tagum City.